2013
DOI: 10.1002/oby.20514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on functional capacity

Abstract: Objective: To assess the relationships between BMI and walking speed, balance control, sit-to-stand performance (a measure of mass specific lower limb power), and endurance. Design and Methods: Thirty-six women with a BMI 30 kg/m 2 and 10 women with normal body weight (BMI between 18 kg/m 2 and 25 kg/m 2 ) were enrolled in this observational study. The obese group comprised 12 persons with a BMI 30 and <35 (obese), 14 subjects with a BMI 35 and <40 (severe obesity) and 10 people with a BMI 40 kg/m 2 (morbid ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 38 publications
4
80
1
15
Order By: Relevance
“…Obese older adults are more likely to fall than others, but the effect of weight on the risk of falling did not appear to be linear (Pataky et al 2014). A longitudinal study by Himes and Reynolds (2012) indicates that obese older adults are more likely to fall than others; moreover, obesity in Class 1 body mass index (BMI) 30.0-34.9 kg/m 2 , and Class 2 BMI 35.0-39.9 kg/m 2 was related to greater likelihood of more disability after a fall, whereas in obesity Class 3 BMI ≥ 40.0 kg/m 2 a protective effect was found, these people are significantly less likely to be injured in a fall than normal-weight individuals.…”
Section: Medell and Alexandermentioning
confidence: 87%
“…Obese older adults are more likely to fall than others, but the effect of weight on the risk of falling did not appear to be linear (Pataky et al 2014). A longitudinal study by Himes and Reynolds (2012) indicates that obese older adults are more likely to fall than others; moreover, obesity in Class 1 body mass index (BMI) 30.0-34.9 kg/m 2 , and Class 2 BMI 35.0-39.9 kg/m 2 was related to greater likelihood of more disability after a fall, whereas in obesity Class 3 BMI ≥ 40.0 kg/m 2 a protective effect was found, these people are significantly less likely to be injured in a fall than normal-weight individuals.…”
Section: Medell and Alexandermentioning
confidence: 87%
“…Comparing our SMWT results with those observed in healthy individuals by Ziegler et al 18 and Burr et al, 19 we found lower distances walked. Pataky et al 6 reported that obese women tend to have slower gait speeds and accompanying shorter stride lengths, relatively less powerful lower limbs and a poorer endurance compared to lean individuals. Comparative studies by Dufek et al 20 and Hergenroeder et al 21 have also shown significantly slower speeds and distances in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence has shown a significant impairment in physical capacity associated with obesity, such as gait disturbances, posture deficits, and greater risk of falling. [2][3][4][5][6] Furthermore, obesity presents a close relationship with chronic degenerative osteoarticular disease, which contributes even more to physical impairment and disability. [4][5][6] There are a few studies evaluating functional abilities, physical capacity, and joint-related symptoms in morbidly obese individuals, as well as their impact on the overall quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Obese subjects move slower and have lower endurance. 7,8 Excess body fat prevents optimal physical performance. 9 In conclusion, energy expenditure is higher in larger subjects due to higher energy expenditure for maintenance.…”
Section: Body Size Body Composition and Energy Expenditurementioning
confidence: 99%